Pembuatan Pompa Air Tanpa Mesin Sebagai Sarana Irigasi Di Dataran Tinggi Pekon Bumi Ratu - Hendri, John; Mulyono, Mulyono; Khotimah, Siti Nurul; Purwadi, Ofik Taupik; Bahri, Syaiful; Laila, Aspita; Ambarwati, Yuli (Pakis Journal Institute, 2024)
Bumi Ratu Village is located on the edge of the Way Sekampung dam, with the position of the dam lower than the village land. This causes the agricultural land and rice fields of Bumi Ratu Village to have difficulty getting water, because the irrigation flow cannot reach a higher position. This problem is an important concern because it greatly affects the planting season and harvest from agriculture. The purpose of this service is to overcome the problem of irrigation of land that has a geographical location above the river level through appropriate technology in the form of a water pump without a machine (hydram pump). The method of this activity consists of several steps, namely 1) Determination of location points that have water sources, 2) Making hydram pump equipment, 3) Socialization, 4) Hydram Pump Trial and 4) Evaluation. This community service activity is expected to be an effective solution in overcoming irrigation problems on their agricultural land. The results of this community service activity show that hydram pumps are an appropriate solution to the irrigation problems that occur in Bumi Ratu Pagelaran Village. Through the use of this hydram pump, farmers and landowners are expected to optimize land irrigation around the highland area so that crop yields can be as expected.